2016
DOI: 10.1177/0884533616653807
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Immune‐Modulatory Intervention in Surgical Patients With Gastric Cancer

Abstract: This study evaluated the effect of an immune-modulatory diet on patients with gastric cancer and identified the parameters associated with postoperative outcomes. This was a single-arm prospective intervention study. At baseline, patients were assessed for nutrition (Patient-Generated Subjective Global Assessment), inflammatory markers (albumin, C-reactive protein, and interleukin 6 [IL-6]), and immune markers (percentage NK, CD4, CD8, and CD4:CD8 ratio); they also received nutrition counseling and high-calori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 35 publications
1
17
0
1
Order By: Relevance
“…In the present study, almost two-thirds (67%) of the patients were malnourished by PGSGA, similar to other studies, showing malnutrition rates of 66% and 57% 26,27 , but lower than the 86% and 88% described in other works [24][25] . Paceli et al 28 found a preoperative weight loss greater than 10% in 42% of gastric cancer patients, similar to those of other Asian studies, of 13% and 31% 6,7 , respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, almost two-thirds (67%) of the patients were malnourished by PGSGA, similar to other studies, showing malnutrition rates of 66% and 57% 26,27 , but lower than the 86% and 88% described in other works [24][25] . Paceli et al 28 found a preoperative weight loss greater than 10% in 42% of gastric cancer patients, similar to those of other Asian studies, of 13% and 31% 6,7 , respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, CD4+/CD8+ is a vital marker that represents total immunity. A decrease in CD4+/CD8+ indicates a compromise of immunologic function and poor prognosis [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recent study showed that high-calorie/protein supplementation with the immune-modulating diet was able to maintain the nutrition and immune status of patients with GC [26]. Furthermore, a study conducted in a population of elderly patients who underwent surgery for GC showed that the combination of enteral and parenteral nutrition was superior to either early enteral nutrition or total parenteral nutrition in promoting the recovery of immunity [27].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%